Trend and Cycles in Coal and Oil Prices in the Long Run: A Schumpeterian Approach - Bloch, Harry; Sapsford, D. (Centre for Research in Applied Economics, Curtin Business School, 2011)
We contribute to the task of identifying trends and cycles in energy prices by examining very long series of prices for coal and oil, going back to 1650 in the case of coal and 1859 in the case of oil. We find annual rates of increase in real price of greater than two percent are found for coal in one cycle, 1842 to 1897, and for oil in two cycles, 1897 to 1953 and 1953 to 2009. However, there is no noticeable change in coal prices for the earliest cycles, from 1675 to 1731 and 1731 to 1787, as well as a notable decline in the latest cycle, from 1953 to 2009. Also, oil prices decline from 1859 to 1897. Clearly, there is no unitary trend across coal and oil that would suggest a general failure of supply due to universal depletion of fossil fuels. Instead, the suggestion is that developments in technology are of critical importance. In particular, the shift in motive power from coal to oil is associated with a rise in the price of oil relative to coal and, in the most recent cycle, a trend decrease in the real coal price.